Trust in Government and Support for Redistribution - Silva, Joana; Morgandi, Matteo; Levin, Victoria (World Bank, Washington, DC, 2016)
In many countries safety nets consist predominantly of universal subsidies on food and fuel. A key question for policy makers willing to shift to targeted safety nets is under what conditions middle-class citizens would be supportive of redistributive programs. Results from a behavioral experiment based on a nationally representative sample in Jordan reveal that increasing transparency in benefit delivery makes middle-class citizens (particularly among the youth and low-trust individuals) more willing to forgo their own welfare to benefit the poor. Moreover, increasing transparency enhances the relative support for cash-based safety nets, which have greater impact on poverty compared with in-kind transfers, but may be perceived as more prone to elite capture.